2012
DOI: 10.1021/ie3014204
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Mass Transfer Rates in Adsorbents: New Combined-Technique Frequency Response Apparatus and Application to CO2 in 13X Zeolite

Abstract: A new combined-technique frequency response apparatus has been developed for studying mass transfer in porous adsorbents. This new apparatus can perform pressure-swing, volume-swing, and concentration-swing frequency response experiments, enabling it to investigate mass transfer of pure components and binary gas mixtures in adsorbents over a wide frequency range. To demonstrate the capabilities of the apparatus, pressure-swing and volume-swing frequency response experiments were performed in tandem to study tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…Hu et al studied the diffusion mechanism of CO 2 in 13X by zero‐length column technique with bead sizes of 1.96 and 3.8 mm and it was found that adsorption of CO 2 was macropore molecular diffusion controlled with contribution from Knudsen diffusion in the low pressure regime. Giesy et al measured the mass transfer rate for CO 2 adsorption on zeolite 13X using frequency response technique for pressures of 0.125, 0.5, and 1 bar and had found that that mass transfer kinetics was well described by the Knudsen diffusion mechanism. In view of these studies, macropore molecular diffusion control was assumed for adsorption kinetics in the present study.…”
Section: Adsorption Equilibrium and Kineticsmentioning
confidence: 99%
“…Hu et al studied the diffusion mechanism of CO 2 in 13X by zero‐length column technique with bead sizes of 1.96 and 3.8 mm and it was found that adsorption of CO 2 was macropore molecular diffusion controlled with contribution from Knudsen diffusion in the low pressure regime. Giesy et al measured the mass transfer rate for CO 2 adsorption on zeolite 13X using frequency response technique for pressures of 0.125, 0.5, and 1 bar and had found that that mass transfer kinetics was well described by the Knudsen diffusion mechanism. In view of these studies, macropore molecular diffusion control was assumed for adsorption kinetics in the present study.…”
Section: Adsorption Equilibrium and Kineticsmentioning
confidence: 99%
“…However, it has limitation on the maximum frequency, which cannot exceed ∼1 Hz, whereas the maximum frequency in a batch system can go up to 100 Hz. Most recent work using such flow‐through techniques has been developed by LeVan and coworkers on pressure‐swing FR (PSFR) and concentration‐swing FR (CSFR) methods that have been used to study mass‐transfer rates for both pure and mixed gases and vapors for various adsorbents: carbon molecular sieves, silica gels, zeolites, metal‐organic frameworks (MOF), and activated carbon materials . Given that each technique has its own advantages and disadvantages, a combined FR apparatus that can perform VSFR, PSFR, and CSFR experiments has been built to be applied to a wider frequency range than VSFR or PSFR alone.…”
Section: Introductionmentioning
confidence: 99%
“…Given that each technique has its own advantages and disadvantages, a combined FR apparatus that can perform VSFR, PSFR, and CSFR experiments has been built to be applied to a wider frequency range than VSFR or PSFR alone. The enhanced experimental capabilities of the apparatus permit more thorough characterization of the dynamic behavior of gas/adsorbent systems …”
Section: Introductionmentioning
confidence: 99%
“…Commercial zeoliteadsorbents are always bound together with clay or alumina to form a composite structure which contains both macropores and micropores, so the mass transfer in the zeolites is controlled by mixture of diffusion mechanisms. Past literatures [34][35][36] has reported that the diffusion of CO 2 in commercial 13X beads is controlled by the mass transport in the macropores, both under Knudsen and molecular diffusion regimes. The increase of gas flow rate results in less contact time for mass transfer, decreasing the recovery of carbon dioxide.…”
Section: Effect Of Vacuum Pressure On Vsa Performancementioning
confidence: 99%